Komunikasi Nabi Muhammad SAW dalam Mendidik Anak - Amalia, Rina Rizki; Aziz, Donny Khoerul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to describe the communication of the Prophet Muhammad SAW in educating children. This study is a qualitative study with a type of library research. Data were collected using documentation techniques and then analyzed using content analysis techniques. The results of the study indicate that there are four steps that parents can take to establish multi-directional communication with their children so that they can produce a democratic, harmonious and dynamic family environment. First, by making the four characteristics of the Prophet Muhammad SAW (shidiq, tabligh, amanah and fathonah) as principles in communicating with children. Second, be gentle when communicating with children. Third, actively communicate by saying hello first when passing in front of the child, inviting them to play together, inviting them to share food, and carrying them. Fourth, be sensitive to children when communicating with them.